Associations between dietary fiber intake and cardiovascular risk factors: An umbrella review of meta-analyses of randomized controlled trials - Fu, Lingmeng; Zhang, Guobing; Qian, Shasha; Zhang, Qin; Tan, Mingming (Frontiers in Nutrition, 2022)
Although several meta-analyses have revealed the beneficial effects of dietary fiber intake on human health, some have reported inconsistent findings. The purpose of this work was to perform an umbrella meta-analysis to evaluate the relevant evidence and elucidate the effect of dietary fiber intake on glycemic control, lipid profiles, systematic inflammation, and blood pressure. Eligible studies were searched in several electronic databases, including Web of Science, PubMed, Scopus, and the Cochrane Library, up to March 2022. A total of 52 meta-analyses involving 47197 subjects were identified to assess the pooled effect size. Overall, higher dietary fiber intake was significantly associated with reductions in parameters involving glycemic control, including fasting plasma glucose (ES=-0.55, 95% CI: -0.73, -0.38, P<0.001), fasting plasma insulin (ES=-1.22, 95% CI: -1.63, -0.82, P<0.001), homeostasis model assessment of insulin resistance (HOMA-IR) (ES=-0.43, 95% CI: -0.60, -0.27, P<0.001), and glycosylated hemoglobin (HbA1c) (ES=-0.38, 95% CI: -0.50, -0.26, P<0.001). In terms of lipid profiles, higher dietary fiber intake was associated with significant reductions in the serum level of total cholesterol (ES=-0.28, 95% CI: -0.39, -0.16, P<0.001) and low-density lipoprotein cholesterol (ES=-0.25, 95% CI: -0.34, -0.16, P<0.001), but not triglycerides (ES=-0.001, 95% CI: -0.006, 0.004, P=0.759) and high-density lipoprotein cholesterol (ES=-0.002, 95% CI: -0.004, 0.000, P=0.087). Higher dietary fiber intake was also significantly associated with improved tumor necrosis factor-alpha serum levels (ES=-0.78, 95% CI: -1.39, -0.16, P=0.013), while no significant effect was observed for C-reactive protein (ES=-0.14, 95% CI: -0.33, 0.05, P=0.156). Finally, blood pressure was also significantly improved following higher dietary fiber intake (systolic blood pressure: ES=-1.72, 95% CI: -2.13, -1.30, P<0.001; diastolic blood pressure: ES=-0.67, 95% CI: -0.96, -0.37, P<0.001). Subgroup analysis revealed that the study population and type of dietary fiber could be partial sources of heterogeneity. In conclusion, the present umbrella meta-analysis provides evidence for the role of dietary fiber supplementation in the improvement of established cardiovascular risk factors.